2008
DOI: 10.1093/humrep/dem404
|View full text |Cite
|
Sign up to set email alerts
|

Placental infection with human papillomavirus is associated with spontaneous preterm delivery

Abstract: HPV infection of extravillous trophoblast induces cell death and may reduce placental invasion into the uterine wall. Thus, HPV infection may cause placental dysfunction and is associated with adverse pregnancy outcomes, including spontaneous preterm delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
184
3
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(205 citation statements)
references
References 25 publications
11
184
3
7
Order By: Relevance
“…These changes in trophoblast function could explain why both HSV-1 and HSV-2 have been associated with spontaneous pregnancy loss (89) and IUGR pregnancies (82,84). AAV2 also induces trophoblast apoptosis and reduces cell invasion (18,90,91) and is associated with spontaneous miscarriage, stillbirth (92), and preeclampsia (82,91,93). Collectively, these results demonstrate that viral infection of the trophoblast can alter placental function and could result in suboptimal conditions for fetal growth and development.…”
Section: Viral Infections and Early Placental Developmentmentioning
confidence: 91%
See 1 more Smart Citation
“…These changes in trophoblast function could explain why both HSV-1 and HSV-2 have been associated with spontaneous pregnancy loss (89) and IUGR pregnancies (82,84). AAV2 also induces trophoblast apoptosis and reduces cell invasion (18,90,91) and is associated with spontaneous miscarriage, stillbirth (92), and preeclampsia (82,91,93). Collectively, these results demonstrate that viral infection of the trophoblast can alter placental function and could result in suboptimal conditions for fetal growth and development.…”
Section: Viral Infections and Early Placental Developmentmentioning
confidence: 91%
“…While not herpesviruses, human papillomaviruses HPV6, -11, -16, -18, and -31 can also infect the extravillous trophoblast (18,19); HPV16 and HPV62 have been identified in gestational week-12 chorionic villus (20); and HPV16, -6, -83, and -39 have been characterized full-term placenta (19,(21)(22)(23). Zika virus (ZIKV) can also infect multiple cell types of the decidua and placenta and will be discussed in further detail in a later section.…”
Section: Viral Infection At the Maternal-fetal Interfacementioning
confidence: 99%
“…The most common and important neoplastic driver of the lower uterine tract, human papillomavirus (HPV), 1 has been detected in the uterine cervix of 15-25% of pregnant women [2][3][4][5][6] and a cervical HPV infection during pregnancy has been associated with a higher incidence of spontaneous abortions, [7][8][9] premature rupture of the membranes, 10 spontaneous preterm labor, 11,12 pre-eclampsia, 13 and placental 'villitis' not otherwise specified. 12 HPV DNA has been detected in the placenta and amniotic fluid.…”
mentioning
confidence: 99%
“…12 HPV DNA has been detected in the placenta and amniotic fluid. 7,11,[14][15][16][17] HPV strains 6,11,16,18, and 31 have been shown to replicate in trophoblast cell lines, [18][19][20] where HPV infection decreased trophoblast number and trophoblast-endometrial cell adhesion in vitro. 19,20 We investigated for the presence of HPV in the placenta and carried out a histopathological and molecular cross-sectional study of 339 placentae from complicated and uncomplicated pregnancies.…”
mentioning
confidence: 99%
“…In fact, authors reported that several cases of idiopathic asthenozoospermia did not present any known risk factor except for the HPV-DNA sperm detection [35,36,81]. Moreover, in vitro evidences show that when HPV is bound to spermatozoa it is potentially transferred to fertilized oocytes, blastocysts, and trophoblast cells [40,9,42]. Even if different studies failed to identify a relationship between early miscarriage/ART failure and HPV positivity in women, new evidences reported a possible role of HPV sperm detection in adverse pregnancy outcome and ART failure [65].…”
Section: Hpv and Fertilitymentioning
confidence: 99%